Prefentif Stres Dalam Perspektif Kesehatan Mental - Zainal, Zainal; Ringgit, Awang; Aprisal, Aprisal; Afrianto, Afrianto; Ernayenti, Ernayenti (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2023)
One of the mental illnesses that can affect humans in modern times is stress. Stress is a mental illness that can cause people to easily experience other illnesses, and can even cause death. The research aims to analyze preventive stress from a mental health perspective according to Islam. This research is library research (library research), this research was carried out by analyzing reading sources in libraries or museums on existing materials in the form of books, magazines, or other documents. The results found several methods of stress therapy according to Islam that can be used by sufferers to regain mental health and peace of mind, namely the potential development method, the faith method, Islam and Ihsan, the takhalli, tahalli, and tajalli methods. In Islam, the essence of stress therapy methods must refer to the Quran which functions as an antidote and mercy for humanity.